A Quality Improvement Project to Reduce Combination Acetaminophen-opioid Prescriptions to Pediatric Orthopedic Patients. Issue 3 (May 2020) - Caruso, Thomas J.; Trivedi, Sunny; Chadwick, Whitney; Gaskari, Shabnam; Wang, Ellen; Marquez, Juan; Lagasse, Sara; Bailey, Madison; Shea, Kevin
Abstract : Background: Acetaminophen-opioid analgesics are among the most commonly prescribed pain medications in pediatric orthopedic patients. However, these combined opioid analgesics do not allow for individual medication titration, which can increase the risk of opioid misuse and hepatoxicity from acetaminophen. The primary aim of this quality improvement project was to alter the prescribing habits of pediatric orthopedic providers at our institution from postoperative acetaminophen-opioid analgesics to independent acetaminophen and opioids. Methods: The study took place in a level 1 trauma center at a children's hospital. A multidisciplinary team of health professionals utilized lean methodology to develop a project plan. Guided by a key driver diagram, we removed acetaminophen-oxycodone products from hospital formulary, implemented a revised inpatient and outpatient electronic order set, and conducted multiple education efforts. Outcomes included inpatient and outpatient percent combined acetaminophen-opioid orders by surgical providers over 27 months. Results: Before the intervention, inpatient acetaminophen-opioid products accounted for an average of 46% of all opioid prescriptions for orthopedic patients. After the intervention and multiple educational efforts, we reported a reduction in the acetaminophen-opioid products to 2.9%. For outpatient prescriptions, combined analgesics accounted for 88% before the intervention, and we reported a reduction to 15% after the intervention. Conclusions: By removing acetaminophen-oxycodone products from hospital formulary, educating the medical staff, and employing revised electronic order sets, the prescribing practice of pediatric orthopedic surgeons changed from the routine use of acetaminophen-opioid analgesics to independent medications.